2020
DOI: 10.1016/j.jcct.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Remission of “mistletoe sign” after treatment

Abstract: We described a 55-year-old man, in whom the first manifestation of retroperitoneal fibrosis (RPF) was only coronary arterial involvement, which had no periaortic or peri-iliac and urinary system retroperitoneum involvement in general and other systemic clinical manifestations. Coronary manifestation was called "mistletoe sign" on the images. Here, we report a case of IgG4-related RPF remission that was only coronary arterial involvement after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Since the previous study demonstrated that steroid therapy might lead to mild regression of the coronary stenosis on CCTA (11), it may also be possible to evaluate the efficacy of coronary periarteritis by comparing the changes of iodine deposition within the tumor-like lesions before and after steroid treatments, thus, providing clinical insight into the characterizations of plaques with an emphasis on the importance of early therapeutic intervention in IgG4-RD involving coronary arteries, such as corticosteroid therapy, surgery, immunomodulators, and immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…Since the previous study demonstrated that steroid therapy might lead to mild regression of the coronary stenosis on CCTA (11), it may also be possible to evaluate the efficacy of coronary periarteritis by comparing the changes of iodine deposition within the tumor-like lesions before and after steroid treatments, thus, providing clinical insight into the characterizations of plaques with an emphasis on the importance of early therapeutic intervention in IgG4-RD involving coronary arteries, such as corticosteroid therapy, surgery, immunomodulators, and immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%